Studies on the Effect of Temperature on the Development of Soft Rot of Cabbage (Brassica oleracea var. Capitata) Caused by Erwinia carotovora sub Sp. Carotovora - Ahmad, M.Y.Zargar, S.A. Mir, M.A. Bhat, K.A. Bhat, S.D. Masoodi, N.A. Bhat, M. (Journal of Phytology, 2010)
Soft rot is one of the destructive diseases of vegetables including cabbage worldwide. Since the temperature is one of the important factors for destructive nature of disease during storage and transportation, experiments were conducted to standardize optimum temperature for the growth of pathogen which revealed pathogen could grow at all the temperatures from 15 to 40°C. Marked higher growth was recorded at 30°C and considerable growth was at 25 and 35°C. During the study of effect of temperature on soft rot disease after 4 and 6 days of storage at different temperatures it was concluded that 30-35°C mostly favor the soft rot in cabbage and thus emphasis is to be given to prevent the disease during the prevailing temperatures in the region, in order to prevent losses due to the disease in cabbage and other hosts of the same pathogen.